Correlation Between Apparent Activation Energy and NOx emission of renewable diesel from sugar cane, biodiesel, fossil diesel and their blends - Conconi, Charles C.; Crnkovic, Paula Cristina Garcia Manoel [UNESP]; Machado, Anibal G.; Pereira, Bernard Muffato; Cortezi, Rogério Augusto Piva; Barros, Jazon (SAE International, 2013)
Biofuels and their blends with fossil fuel are important energy resources, which production and application have been largely increased internationally. This study focus on the development of a correlation between apparent activation energy (Ea) and NOx emission of the thermal decomposition of three pure fuels: farnasane (renewable diesel from sugar cane), biodiesel and fossil diesel and their blends. Apparent Activation energy was determined by using thermogravimetry and Model-Free Kinetics. NOx emission was obtained from the European Stationary Cycle (ESC) with OM 926LA CONAMA P7/Euro 5 engine. Results showed that there is a linear correlation between apparent activation energy and NOx emission with R2 of 0,9667 considering pure fuels and their blends which is given as: NOx = 2,2514Ea - 96,309. The average absolute error of this correlation is 2.96% with respect to the measured NOx value. The main advantage of this correlation is its capability to predict NOx emission when either a new pure fuel or a blend of fuels is proposed to use in enginees.